2019
DOI: 10.3390/pr7110775
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Batch Slow Pyrolysis of Biomass Materials Using the Process-Flow-Diagram COCO Simulator

Abstract: The commercial COCO simulation program was used to mimic the experimental slow pyrolysis process of five different biomasses based on thermodynamic consideration. The program generated the optimum set of reaction kinetic parameters and reaction stoichiometric numbers that best described the experimental yields of solid, liquid and gas products. It was found that the simulation scheme could predict the product yields over the temperature range from 300 to 800 • C with reasonable accuracy of less than 10% averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…The approach is illustrated in Section 3.1. From Figure 6 and Tables 7 and 8, we can see the scope of Sp ≥ 3 has covered the major part of the Kumar model with the criterion listed in Formula (17). (As the result of our experience the threshold value TV is set as 80%).…”
Section: Case Backgrounds and Conditionsmentioning
confidence: 96%
See 2 more Smart Citations
“…The approach is illustrated in Section 3.1. From Figure 6 and Tables 7 and 8, we can see the scope of Sp ≥ 3 has covered the major part of the Kumar model with the criterion listed in Formula (17). (As the result of our experience the threshold value TV is set as 80%).…”
Section: Case Backgrounds and Conditionsmentioning
confidence: 96%
“…IV ≥ (17) Formula (17) shows the criterion of minimum value of Sp value. The approach is presented in Figure 5.…”
Section: Minimum Scope Screened Out Via Ipr Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…A non-exhaustive survey of biomass pyrolysis modeling utilizing Aspen Plus from 2010 to 2021 found that approximately 63% of biomass pyrolysis simulations applied thermodynamic equilibrium models, and that the most-cited subset of this approach is the method relying on the minimum Gibbs free energy (MGFE) [30][31][32][33][34][35][36][37][38][39][40][41][42][43]. The remaining 14% and 23% used the kinetic approach [44][45][46] and FD [47][48][49][50][51], respectively (see Figure 2b). cesses, and it paves the way to establishing a simple model that contains the primary pyrolysis reactions [9,27].…”
Section: Approaches For Modeling Of Pyrolysis and Simulation In Aspen...mentioning
confidence: 99%
“…This software allows editing the operational variables defined through the CAPE-OPEN standard, allowing interoperability [9]. Several authors performed simulations using COCO simulator software to study the bio-waste handling systems [10][11][12] and bio-waste pyrolysis. Onarheim et al [13] simulated the fast pyrolysis of pine and forest residues for bio-oil production.…”
Section: Introductionmentioning
confidence: 99%